The multifunctional Ca2+/Calmodulin-dependent kinase II [delta] (CaMKII[delta]) Controls Neointima Formation after Carotid Ligation and Vascular Smooth Muscle Cell Proliferation through Cell Cycle Regulation by p21 - Li, Weiwei; Li, Hui; Sanders, Philip N.; Mohler, Peter J.; Backs, Johannes; Olson, Eric N.; Anderson, Mark E.; Grumbach, Isabella M. (The journal of biological chemistry, 2011)
The multifunctional Ca2+/calmodulin-dependent protein kinase II (CaMKII) promotes vascular smooth muscle (VSMC) proliferation. However, the signaling pathways mediating CAMKII-dependent proliferative effects in vivo are poorly understood. This study tested the hypothesis that CaMKIIδ mediates neointimal proliferation after carotid artery ligation by regulating expression and activity of cell cycle regulators, particularly at the G1/S checkpoint. Data herein indicate that 14 days after carotid ligation, C57Bl/6 mice developed a marked neointima with robust CaMKII protein expression. In particular, only the CaMKII isoform δ was increased as demonstrated by quantitative RT-PCR. Genetic deletion of CaMKII δ prevented injury-induced neointimal hyperplasia and cell proliferation in the intima and media. In ligated carotids of control mice, the proliferative cell cycle markers cdk2, cyclin E, and cyclin D1 were activated. In contrast, in CaMKIIδ−/− mice, we detected a reduction in proliferative cell cycle regulators as well as an increase in the cell cycle inhibitor p21. This expression profile was confirmed in cultured CaMKIIδ−/− VSMC, in which cdk2 and cdk4 activity was decreased. Toward understanding how CAMKIIδ affects p53, a transcriptional regulator of p21, we examined p53 pathway components. Our data indicate that p53 is elevated in CAMKIIδ−/− VSMC, whereas phosphorylation of the p53-specific E3 ligase, Mdm2, was decreased. In conclusion, CaMKII stimulates neointima proliferation after vascular injury by regulating cell proliferation through inhibition of p21 and induction of Mdm-2-mediated degradation of p53.